2017
DOI: 10.1111/gtc.12511
|View full text |Cite
|
Sign up to set email alerts
|

Generation of biallelic F0 mutants in medaka using the CRISPR/Cas9 system

Abstract: Several animal models generated by genome editing methods develop somatic mosaic mutations including wild-type genome sequence in F0 generation because it is difficult to use editing tools at the one-cell stage. Producing complete knockout animals quickly is a great advantage in determining the function of target genes. This study investigated the generation of F0 knockout medaka using the CRISPR/Cas9 system. To determine whether this editing system induced mutations in the medaka genome at the one-cell stage,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
22
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 25 publications
1
22
0
Order By: Relevance
“…To investigate whether the immortalized hybridomas express the gonadal somatic cell markers, we examined germ cell and gonadal somatic cell markers using the hybridomas cultured for 3 weeks. qRT-PCR showed that the germ cell marker dead end (dnd) ( 32 ) was not expressed in any of the cell lines examined in this study ( Figure 4E ). Conversely, the Sertoli cell marker mis was expressed weakly in FOT-01 and FOT-02, and strongly in OLHE-131 ( Figure 4F ).…”
Section: Resultsmentioning
confidence: 83%
See 1 more Smart Citation
“…To investigate whether the immortalized hybridomas express the gonadal somatic cell markers, we examined germ cell and gonadal somatic cell markers using the hybridomas cultured for 3 weeks. qRT-PCR showed that the germ cell marker dead end (dnd) ( 32 ) was not expressed in any of the cell lines examined in this study ( Figure 4E ). Conversely, the Sertoli cell marker mis was expressed weakly in FOT-01 and FOT-02, and strongly in OLHE-131 ( Figure 4F ).…”
Section: Resultsmentioning
confidence: 83%
“…A small laboratory fish with an XX/XY sex determination system, it has advantages such as a short generation time, small genome size, and several useful strains are available ( 29 ). Additionally, transgenesis, knockdown techniques, and genome editing using clustered regularly interspaced short palindromic repeats (CRISPR)/CRISPR-associated protein 9 have been established ( 30 32 ). Medaka is therefore a valuable vertebrate model for the analysis of the molecular genetics of various biological phenomena, including embryonic development and sex differentiation.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, Decode-seq also identified the germ cell marker vasa as a DEG in the top 300 list. Lastly, we knocked out a novel DEG (ENSORLG00000007290) using a rapid knockout method to generate F0 mutants [27,28]. The mutant showed severe germ cell depletion ( Fig.…”
Section: Identification Of Differentially Expressed Genes (Degs)mentioning
confidence: 99%
“…One of the challenges of applying CRISPR/Cas9 methodologies in poikilothermic species like fish is that temperature conditions in vivo will be suboptimal for Streptococcus pyogenes Cas9 (SpCas9) activity which is optimal at 37 °C 19 . Although editing activity with the CRISPR/Cas9 has been reported in tropical species like zebrafish, medaka and Nile tilapia at 26-28 °C 13,15,20 , the apparent diversity in resultant individual genotypes requires careful analysis and interpretation. To date, CRISPR/Cas9-mediated sterility studies have lacked a comprehensive screening and understanding of genotypes generated in F0 animals due to biased mutant screening methods, lack of standardisation and/or methodological details.…”
mentioning
confidence: 99%
“…The lack of understanding of the resultant mutations including the level of mosaicism and the indel spectrum hinders the direct functional analysis in the injected animals. The most frequently used screening methods in gonad-related gene functional studies have been restriction enzyme digestion (RED) and Sanger sequencing of a limited number of cloned sequences [8][9][10][11][12][13]15,[21][22][23] , with a few studies adopting high resolution melt curve analysis (HRMA) or SURVEYOR techniques 24,25 . Such approaches have a number of potential limitations in their accuracy to describe KO effects on target genotypes, which are further confounded by the pooling of samples which ultimately provides a biased interpretation of the efficacy of CRISPR/Cas9 gene editing in this field.…”
mentioning
confidence: 99%